THE PRINCIPLE OF THE BEST INTERESTS IMPLEMENTATION OF THE CHILD IN A DECISION TO CANCEL A CHILD'S BIRTH CERTIFICATE - Rizky Mustika; I Made Pria Dharsana (Jurnal Pembaharuan Hukum, 2023)
This research aims to provide an understanding of the determination to cancel a child's birth certificate that can potentially violate children's human rights. So that the role of judges as a judicial institution is needed to protect children's rights as it should. Marriage registration is merely an administrative action and does not affect the validity of the marriage. Errors in marriage registration should not necessarily affect the status of the child's position. Because after all, birth certificates are issued by the state to protect and provide legal certainty over the child's status. This research used a typology of research with a prescriptive form and then normative juridical research methods with secondary data derived from laws and regulations relating to child protection. In conclusion, legal action to cancel a child's birth certificate due to legal defects in a marriage can be said to be an action that is contrary to the principle of the best interests of the child, therefore it is fitting that the application for annulment of a child's birth certificate be properly considered by the panel of judges who act as an extension of the state in the judicial field.